Changes in HCFC Emissions in China During 2011–2017. Issue 16 (19th August 2019) - Fang, X.; Yao, B.; Vollmer, M. K.; Reimann, S.; Liu, L.; Chen, L.; Prinn, R. G.; Hu, J.
Abstract: Hydrochlorofluorocarbons (HCFCs), the main substitutes of chlorofluorocarbons, are regulated by the Montreal Protocol. Chinese HCFC emissions increased fast from the beginning of this century. However, limit reports based on atmospheric measurement are available for years after 2011, an important period when significant changes are expected. Combining atmospheric observations at seven sites across China with a FLEXible PARTicle dispersion model‐based Bayesian inversion technique, we estimate emission magnitudes and changes of four major HCFCs in China during 2011–2017. The emissions of all four HCFCs reached peaks before 2015. Our results agreed well with the reported bottom‐up inventories. The Chinese ozone depletion potential (ODP)‐weighted emission of the three most abundant HCFCs accounted for 37% of global totals from 2011 to 2016. The total emission of HCFC‐22 from China, the European Union, and the United States accounted approximately a half of the global totals, suggesting large HCFC emission emitted from the rest of the world. Plain Language Summary: Hydrochlorofluorocarbons (HCFCs) are used to replace chlorofluorocarbons, or well known as Freon, a group of gases which contribute to the polar ozone hole. However, HCFCs are also important ozone depletion substances and are regulated by the Montreal Protocol. As the largest developing country, the HCFC emissions in China are of great interest. In this study, we estimate emission magnitudes and changes of four major HCFCs in China over the period 2011–2017 based on atmospheric observations at seven sites. We find the emissions of all four HCFCs reached their peaks before 2015, which generally agree with the emission inventories estimated using production and consumption information, suggesting the effectiveness of the implementation of Montreal Protocol in China. However, there is a big gap between the total HCFC‐22 emission from China, the European Union, and the United States and global totals, suggesting large emissions from the rest of the world. Key Points: The Chinese emissions of HCFC‐22, HCFC‐141b, HCFC‐142b, and HCFC‐124 all reached peaks before 2015 The Chinese ODP‐weighted emission of the three most abundant HCFCs accounted for 37% of global totals from 2011 to 2016 Large gaps were found between the global HCFC‐22 emissions and total HCFC‐22 emissions from the European Union, the United States, and China